Diffusion of Innovations, 5th Edition - Rogers, Everett M. (Free Press, 2003)
Now in its fifth edition, Diffusion of Innovations is a classic work o n the spread of new ideas.In this renowned book, Everett M. Rogers, pr ofessor and chair of the Department of Communication & Journalism at t he University of New Mexico, explains how new ideas spread via communi cation channels over time. Such innovations are initially perceived as uncertain and even risky. To overcome this uncertainty, most people s eek out others like themselves who have already adopted the new idea. Thus the diffusion process consists of a few individuals who first ado pt an innovation, then spread the word among their circle of acquainta nces—a process which typically takes months or years. But there are ex ceptions: use of the Internet in the 1990s, for example, may have spre ad more rapidly than any other innovation in the history of humankind. Furthermore, the Internet is changing the very nature of diffusion by decreasing the importance of physical distance between people. The fi fth edition addresses the spread of the Internet, and how it has trans formed the way human beings communicate and adopt new ideas.